Self-Guided Analysis Tool Pack (S-Gat) Improved Students’ Performance in Statistics: Experimental Approach - Kristian James S Ramos; Sherwin B Sapin; Alberto D Yazon; Victoria E Tamban; Glen P Cortezano (Research Synergy Foundation, 2023)
Nowadays, there are different platforms, applications, and software available, yet it is not implemented nor integrated into the class discussion as part of teaching and learning. SPSS, Jamovi, and even Microsoft Excel are some that may be used by the students for the statistical treatment of data. Students are lacking the advantage to be equipped with technology in this kind of situation. They are becoming incompetent to other students who have the skills in using the different applications as mentioned above.This study aimed to determine the effectiveness of Self-guided Analysis Tool Pack (S-GAT) as a supplementary material in improving students’ performance in Statistics. The researcher used quasi-experimental research. The respondents were selected Grade 12 students. Two sections were selected as the comparison and experimental group. From these participants, the researcher match-paired the scores in pretest as basis to form the students under comparison group and those in experimental group. The prescribed module was used by the comparison group while the experimental group utilized SGAT. The statistical tools used were the weighted mean, Standard Deviation, Independent Samples t-test and Paired Samples T-test. The researcher also utilized Cohen’s d to determine the effect size. Findings revealed that S-GAT and prescribed module improved students’ performance in Statistics. Both groups had improvement in their performance revealed in their posttest scores, however, students who used SGAT had significantly higher performance than those who used the prescribed module as revealed in the posttest scores. S-GAT is effective and may be utilized as supplementary material in Statistics. Thus, the researcher encouraged other teacher-researchers to innovate technology-based instructional materials to enhance the student’s performance in general.